Selective and sensitive GC-MS analysis of carcinogenic N-nitrosodimethylamine in pharmaceuticals using a magnetic coconut carbon composite as a solid-phase extraction sorbent - Hazim M. Ali; Ibrahim Hotan Alsohaimi; Mohammad Rizwan Khan; Ibrahim A. Naguib; Rosa Busquets; Pravej Alam; Bayan E. Ainousah; Mohammed Gamal (Journal of Taibah University for Science, 2023)
The aim of the present research was to develop a magnetic coconut carbon composite (Fe2O3/Fe3O4@CNC) as a solid-phase extraction (SPE) sorbent for the analysis of carcinogenic N-nitrosodimethylamine (NDMA) in pharmaceuticals. Coconut composites modified with Fe2O3 and Fe3O4 were prepared and applied as SPE sorbent for the extraction of NDMA in pharmaceuticals. The sorbent was characterized with X-Ray, infrared spectroscopy and nitrogen porosimetry. The best ions for the Gas Chromatography-Mass Spectrometry with Selected Ion Monitoring (GC-MS/SIM) analysis were m/z 74 and 42 for NDMA, and m/z 80 and 46 for NDMA-d6 internal standard. System has offered great method performance in terms of sensitivity limit of quantitation (LOQ) 16 ng kg−1. The developed sorbent has enhanced the sensitivity and speed of analysis. The developed method was applied to authenticate the presence of NDMA in various pharmaceutical samples. Among the analyzed samples, NDMA impurities were relatively identified at high amounts in nizatidine samples.Highlights NDMA was verified in ranitidine, metformin and nizatidineFe2O3/Fe3O4@CNC composite was used for NDMA identification without pretreatmentSPE sorbent enhance sensitivity, reduce analysis time, sustain accuracy & precisionHigh level of NDMA impurity were found in nizatidine pharmaceuticals.